2004
DOI: 10.1016/s0006-3495(04)74219-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Lack of a Specific Interaction between Cholesterol and Sphingomyelin

Abstract: The putative specific interaction and complex formation by sphingomyelin and cholesterol was investigated. Accordingly, low contents (1 mol % each) of fluorescently labeled derivatives of these lipids, namely 1-palmitoyl-2[10-(pyren-1-yl)]decanoyl-sn-glycero-3-phosphocholine (PyrPC), n-[10-(1-pyrenyl)decanoyl]sphingomyelin (PyrSM), and increasing concentrations of cholesterol (up to 5 mol %), were included in large unilamellar vesicles composed of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) or 1,2-diner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 73 publications
4
70
1
1
Order By: Relevance
“…For example, both formulations account for the poor attack of cholesterol oxidase on mixed bilayers containing phospholipids with head groups that would shield sterols [5,57]. Furthermore, each mechanism could drive the condensation of phospholipid-sterol mixtures [58]. Both models serve the present argument by predicting an equivalence point in activity when phospholipids are titrated with sterols as well as the high activity of the excess free sterol monomers beyond this point.…”
Section: The Source Of High-activity Cholesterol In Bilayersmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, both formulations account for the poor attack of cholesterol oxidase on mixed bilayers containing phospholipids with head groups that would shield sterols [5,57]. Furthermore, each mechanism could drive the condensation of phospholipid-sterol mixtures [58]. Both models serve the present argument by predicting an equivalence point in activity when phospholipids are titrated with sterols as well as the high activity of the excess free sterol monomers beyond this point.…”
Section: The Source Of High-activity Cholesterol In Bilayersmentioning
confidence: 89%
“…In contrast, another molecular dynamics study concluded that the rough and smooth surfaces of the sterol were critical to how it organized the bilayer phospholipids laterally [47]. Finally, a lack of specificity in the interaction of cholesterol with sphingomyelin, considered to be its strongest membrane partner, has been inferred from detailed fluorescence studies [58]. Rather than specific associations, it has been suggested that congregation to minimize hydrophobic mismatch between the sterol and alkyl chains could be a driving force in their association [10,12].…”
Section: Sterol Specificitymentioning
confidence: 99%
“…We found that the major phospholipid components were long chain phosphatidylcholines (PC) and SMs. The long chain PCs and SMs likely caused ordering of the lens fi ber membranes and allowed for more interactions between phospholipids and cholesterol ( 17 ).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Approximately four times more CTAB was required to promote the same CR (40%) in the PDA/ CHO/SPH system compared to PDA vesicle. This behavior is explained by vesicle rigidity caused due to interaction between CHO and SPH molecules [32] and between them and with PDA via hydrogen bonding [33]; thus PDA/CHO/SPH were more thermodynamically stable structures [34] than pure PDA nanostructure.…”
Section: Polydiacetylene Vesicles For Detecting Surfactants: Understamentioning
confidence: 99%